Therapeutic drug monitoring of long-acting injectable antipsychotic drugs - Schoretsanitēs, Geōrgios; Baumann, Pierre; Conca, Andreas; Dietmaier, Otto; Giupponi, Giancarlo; Gründer, Gerhard; Hahn, Martina; Hart, Xenia Marlene; Havemann-Reinecke, Ursula; Hefner, Gudrun; Kuzin, Maxim; Mössner, Rainald; et al. (Therapeutic drug monitoring, 2021)
Background: The use of therapeutic drug monitoring (TDM) to guide treatment with long-acting injectable (LAI) antipsychotics, which are increasingly prescribed, remains a matter of debate. The aim of this review was to provide a practical framework for the integration of TDM when switching from an oral formulation to the LAI counterpart, and in maintenance treatment. Methods: The authors critically reviewed 3 types of data: (1) positron emission tomography data evaluating dopamine (D2/D3) receptor occupancy related to antipsychotic concentrations in serum or plasma; D2/D3 receptors are embraced as target sites in the brain for antipsychotic efficacy and tolerability, (2) pharmacokinetic studies evaluating the switch from oral to LAI antipsychotics, and (3) pharmacokinetic data for LAI formulations. Based on these data, indications for TDM and therapeutic reference ranges were considered for LAI antipsychotics. Results: Antipsychotic concentrations in blood exhibited interindividual variability not only under oral but also under LAI formulations because these concentrations are affected by demographic characteristics such as age and sex, genetic peculiarities, and clinical variables, including comedications and comorbidities. Reported data combined with positron emission tomography evidence indicated a trend toward lower concentrations under LAI administration than under oral medications. However, the available evidence is insufficient to recommend LAI-specific therapeutic reference ranges. Conclusions: Although TDM evidence for newer LAI formulations is limited, this review suggests the use of TDM when switching an antipsychotic from oral to its LAI formulation. The application of TDM practice is more accurate for dose selection than the use of dose equivalents as it accounts more precisely for individual characteristics.
Gesehen am 01.07.2021